2022
DOI: 10.1080/22221751.2022.2088407
|View full text |Cite
|
Sign up to set email alerts
|

Global dissemination of H5N1 influenza viruses bearing the clade 2.3.4.4b HA gene and biologic analysis of the ones detected in China

Abstract: H5N1 avian influenza viruses bearing the clade 2.3.4.4b hemagglutinin gene have been widely circulating in wild birds and are responsible for the loss of over 70 million domestic poultry in Europe, Africa, Asia, and North America since October 2020. During our routine surveillance, 13 H5N1 viruses were isolated from 26,767 wild bird and poultry samples that were collected between September 2021 and March 2022 in China. To investigate the origin of these Chinese isolates and understand their genetic relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 57 publications
(38 reference statements)
1
67
0
Order By: Relevance
“…Since then, it has been persistently circulating in this geographic area, and in West Africa it reassorted with the A(H9N2) subtype of the zoonotic G1 lineage (Ouoba et al, 2022). Starting from October 2021, different A(H5N1) genotypes, some of them previously identified in Europe, have been detected in South and East Asia, including China (Cui et al, 2022). In December 2021, North America announced the first detection of an A(H5N1) virus strongly related to the A(H5N1) identified in Northern Europe during the 2020-2021 epidemic season (Bevins et al, 2022;Caliendo et al, 2022b).…”
Section: Description Of the Nomenclature Of The Hpai A(h5) Viruses Us...mentioning
confidence: 95%
“…Since then, it has been persistently circulating in this geographic area, and in West Africa it reassorted with the A(H9N2) subtype of the zoonotic G1 lineage (Ouoba et al, 2022). Starting from October 2021, different A(H5N1) genotypes, some of them previously identified in Europe, have been detected in South and East Asia, including China (Cui et al, 2022). In December 2021, North America announced the first detection of an A(H5N1) virus strongly related to the A(H5N1) identified in Northern Europe during the 2020-2021 epidemic season (Bevins et al, 2022;Caliendo et al, 2022b).…”
Section: Description Of the Nomenclature Of The Hpai A(h5) Viruses Us...mentioning
confidence: 95%
“…It was confirmed that two types of H5 viruses with different hemagglutinin (HA) in the genetic pool were already circulating in autumn 2021; one had been continuously present with genetic drift among the European bird population since autumn 2020, and the other, which originated in African countries but could be widely spread throughout European countries [ 8 ] had been detected since October 2021. Under such a circumstance, many gene-reassorted viruses, including H5N1, were generated, and dominant H5N1 reassorted viruses were further transferred from Europe to African, North American, or Asian countries in winter 2021–2022 [ 9 , 10 , 11 , 12 ]. Phylogenetic analyses have already revealed that two types of H5 HPAIVs invaded southern Japan at the end of 2021.…”
Section: Introductionmentioning
confidence: 99%
“…The global spread of viral pathogens, such as IAV and SARS-CoV-2, led to major economic and health challenges worldwide [42][43][44]. Revealing host genes essential for infection by IAV can provide insights into the virus pathogenesis, and facilitate the development of novel therapeutics.…”
Section: Discussionmentioning
confidence: 99%